Seismic behavior of superimposed reinforced concrete shear walls with X‐shaped steel plate bracings under different axial load ratios. (19th August 2021) - Wang, Mengfu; Guo, Shengqi
Summary: In order to improve the seismic performance of traditional superimposed reinforced concrete shear walls, a kind of superimposed reinforced concrete shear wall with X‐shaped steel plate bracings (labeled as SRCXSW) was proposed in this paper. And seismic behaviors of three 1/2‐scale shear walls including two SRCXSWs with different axial load ratios (ALRs) and one cast‐in‐place reinforced concrete shear wall with X‐shaped steel plate bracings (labeled as CRCXSW) were investigated by the quasi‐static loading test. Experimental results indicated that SRCXSW and CRCXSW with the same ALR exhibited the similar seismic behaviors, different ALRs applied in SRCXSW greatly affected the seismic behaviors in terms of load‐bearing capacity, deformation, lateral stiffness, and energy dissipation capacity and slightly affected the failure mode and cooperative mechanism between the precast and cast‐in‐place concrete layers. In particular, a high ALR applied on SRCXSW had little effect on the stiffness degradation before yielding, but accelerated the post‐yield stiffness degradation. Then, based on the discussion conclusion about the contribution of three mechanisms to the load‐bearing capacity varying with aspect ratio, a modified strut‐and‐tie model for predicting the maximum strength of specimens was proposed, and good predictive ability under different ALRs was verified by experimental and finite element analysis (FEA) results. Besides, FEA based on OpenSees was implemented to further investigate the effect of critical parameters, FEA results showed that ALR and longitudinal reinforcement ratio in boundary element had a significant influence on the load‐bearing capacity and deformation capacity of SRCXSW. And a higher volumetric ratio of X‐shaped steel plate bracings and longitudinal reinforcement ratio in boundary element led to a greater load‐bearing capacity but their contribution decrease with the increase of ALR.